Enzymatic Activity and Physicochemical Properties of Soil Profiles of Luvisols - Anna Piotrowska-Długosz (MDPI AG, 2021)
Most studies on soil enzymes are focused on the upper horizons of the soil profile, even though they transform the soil organic matter at every depth of the soil profile. The aim of this work was to investigate the distribution of β-glucosidase (GLU), nitrate reductase (NR), urease (UR), phosphatase (PHA), dehydrogenase (DHA) and catalase (CAT) activity through 14 trunked soil profiles of the Luvisols formed from a glacial till. The content of microbial biomass carbon (MBC) as well as physicochemical properties such as organic carbon (CORG), total nitrogen (NTOT), available P, K and Mg, soil density and porosity, pH in KCl and fractional composition were also studied. In general, enzymatic activity was highest in the top 30 cm layer of the profiles and decreased progressively towards the deeper horizons. The exceptions were the NR activity, which was active only in the Ap horizon and whose activity decreased sharply to nearly zero in the Bt horizon and parent rock, and the PHA activity, which was highly active even in the parent rock depth. The decreased availability of carbon and nutrients was the main driver of decreases in microbial abundance and enzymatic activity with depth. The enzymatic activity, when expressed on a CORG and MBC basis, behaves differently compared to the activity expressed on a soil mass basis. The activity decreased (NR), increased (PHA, UR), showed no clear pattern (GLU) or the changes were not significant (DHA, CAT). The content of CORG, NTOT, K and PAVAIL generally decreased with depth, while for Mg, there was no clear direction in the profile distribution. Future studies to characterize the substrate distribution within the soil profile and enzyme stability will provide further insight into the controls on nutrient cycling and related enzymes throughout the soil profiles.